Using non-organic resist based on As-S-Se chalcogenide glasses for combined optical/digital security devices - Kostyukevych, S.A.; Moskalenko, N.L.; Shepeliavyi, P.E.; Girnyk, V.I.; Tverdokhleb, I.V.; Ivanovsky, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Modern holographic protective elements used as emblems against counterfeiting are being more complicated as they should oppress criminal world. 2D, 3D, 3D rainbow holograms or simple diffraction structures protecting documents can not be acceptable against illegal copying of important documents, bank notes or valuable products. Recent developments in technology of Optical variable devices permit world leaders to create more advanced security elements: Kinegrams™, Exelgrams™, Pixelgrams™, Kineforms™. These products are used for protecting the most confidential documents and bank notes, but now even their security level can not be enough, and besides their automatic identification is vulnerable to factors of instability. We elaborate new visual security devices based on the usage of expensive and advanced technology of Combined optical/digital security devices. The technology unites digital and analog methods of synthesis and recording Visual security devices. The analog methods include technique of optical holography - different combinations of 2D/3D, 3D, 2D/3D + 3D structures. Basing on them the design with elements of 3D graphic including security elements and hidden machine-readable images are implemented. The digital methods provide synthesis of Optical Variable Devices including special security elements, computer generated holograms and Kineforms™. Using them we create determined and quasi-random machine-readable images. Recording are carried out using the combined optical and electron-beam submicrometer technology. The results obtained show effectiveness of the combined technology permitting to increase the security level essentially that should increase tamper and counterfeit resistance for many years.